Effector Functions of CD4+ T Cells at the Site of Local Autoimmune Inflammation—Lessons From Rheumatoid Arthritis - Chemin, Karine; Gerstner, Christina; Malmström, Vivianne (Frontiers in Immunology, 2019)
Infiltration of memory CD4+ T cells in synovial joints of Rheumatoid Arthritis (RA) patients has been reported since decades. Moreover, several genome wide association studies (GWAS) pinpointing to a key genetic association between the HLA-DR locus and RA have led to the generally agreed hypothesis that CD4+ T cells are directly implicated in the disease. Still RA is a heterogeneous disease and much effort has been put into understanding its different facets. Importantly, T cell differentiation are driven by mechanisms including antigen stimulation, co-stimulatory signals and cytokine milieu which all are abundant in the rheumatic joint, implicating that any T cells migrating into the joint may be further affected locally. Hence, in parallel to the characterization and classification of T cell subsets, the contribution of different effector T cells to RA has been investigated in numerous studies and sometimes with contradictory results. In particular, the frequency of Th1 and Th17 cells has been assessed in the synovial joints with various results that could at least partly be explained by the stage of the disease. For regulatory T cells, it is largely accepted that they accumulate in RA synovial fluid and that the equilibrium between regulatory T cells and effector cells is a key factor to control inflammation processes involved in RA. Recent phenotypic studies describe the possible implication of a novel subset of peripheral T helper cells (Tph) important for T-B cell cross talk and plasma cell differentiation in the RA joint of ACPA+ (autoantibodies against citrullinated proteins) RA patients. Finally, cytotoxic CD4+ T cells, historically described as increased in RA patients have attracted new attention in the last years. In view of the recently identified peripheral T cell subsets, we will integrate immunological data, information on genetic variants and therapeutic strategy outcomes into our current understanding of the width of effector T cells. We will also integrate resident memory T cell aspects and discuss similarities and differences with inflammatory conditions in skin (psoriasis) and mucosal organs (Crohn´s disease).